If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 31 = 7x + -18 Reorder the terms: 31 = -18 + 7x Solving 31 = -18 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 31 + -7x = -18 + 7x + -7x Combine like terms: 7x + -7x = 0 31 + -7x = -18 + 0 31 + -7x = -18 Add '-31' to each side of the equation. 31 + -31 + -7x = -18 + -31 Combine like terms: 31 + -31 = 0 0 + -7x = -18 + -31 -7x = -18 + -31 Combine like terms: -18 + -31 = -49 -7x = -49 Divide each side by '-7'. x = 7 Simplifying x = 7
| 2m+m+23-14=3(m+3) | | 6+19n-3=9n+71-7n | | 27-(2x+9)=2(x+4)+x | | 5x=7(6+4) | | 13=3(x-1)-(x-6) | | 4+5[14-2(3+2)]= | | 3a+20=2 | | 15+4a=27 | | lnx=1.5 | | 3y+7=910 | | 4y-4+8=8y+40-5y | | 12x+50=180 | | -13m=52 | | 11.697083+7(5.1529)+25(2.27)-39= | | 15x^2+11x-35=0 | | 5(3+4x)-2=113 | | 792=-33i | | -2m=144 | | -8(-8x-6)=-6x-22x | | -1+x=y | | 2w+8(4+3)=34 | | 27+5*8-6=37 | | h^2+12th+27=0 | | 8(4k-4)=-5h-32k | | 60x^2-66x+6=0 | | 3x-14x+25=0 | | 6n-18=-14+7n | | 0.7h=-0.1212 | | 9-4y+16+y=4 | | 2x+(-5)y-6=8 | | 4x-24=-12+2x | | -10x-22=-172 |